1989
DOI: 10.1111/j.1699-0463.1989.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cardiac metastasis

Abstract: A review of 8571 autopsies disclosed 2833 patients with malignant tumours from 1975 to 1984 at the Department of Pathology, The Gade Institute. Cardiac metastases were found in 130 cases. An increase of cardiac involvement was shown in the autopsy material from I . 2% in 1975-1979 to I .8% in 1980-1984. The same trend was seen if cardiac metastases were related to malignant tumours. Numerically, lung cancer accounted for most of the metastases seen, but the increase was made up by other tumours than lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Twenty-two percent of the patients had no metastases present at the time of death. Of note, melanoma has a relatively high incidence of cardiac metastases [32] and a rare isolated case of a left atrial metastasis in the setting of a primary esophageal melanoma was recently reported [33].…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-two percent of the patients had no metastases present at the time of death. Of note, melanoma has a relatively high incidence of cardiac metastases [32] and a rare isolated case of a left atrial metastasis in the setting of a primary esophageal melanoma was recently reported [33].…”
Section: Discussionmentioning
confidence: 98%
“…With increased longevity, a trend of increased incidence of CM has been shown in different studies. [5][6][7] Because of the above-mentioned factors, together with the widespread use of modern imaging techniques, an increase in the frequency of the antemortem diagnosis of CM is to be expected in the near future.…”
Section: Case Reportmentioning
confidence: 99%
“…3 The incidence of cardiac metastases reported in literature is highly variable, ranging from 2.3% and 18.3% (table 1). [3][4][5][6][7][8][9][10][11][12][13][14] Although no malignant tumours are known which diffuse preferentially to the heart, some do involve the heart more often than others-for example, melanoma and mediastinal primary tumours. Therefore, as for every other site, the tumour's ability to spread to the heart depends on several factors, not only the characteristics of the primary tumour but also the specific histological and functional characteristics of the heart.…”
mentioning
confidence: 99%